2012
DOI: 10.1590/s1516-31802012000600002
|View full text |Cite
|
Sign up to set email alerts
|

Changes in mastectomy rates at a Brazilian public hospital over 20 years (1989 to 2008)

Abstract: CONTEXT AND OBJECTIVE: Recently, breast-conserving surgery (BCS) has been replacing mastectomy for breast cancer treatment. The aim of this study was to evaluate the changes in mastectomy and BCS rates and the factors relating to these shifts. A shift from mastectomy towards BCS was observed (P < 0.001). In multivariate analysis, earlier year of surgery (P < 0.001), larger tumor size (P < 0.001), having at least one positive axillary lymph node (P < 0.001) and patients' age greater than 68 years (P = 0.007) we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…In our study, the frequencies of stages did not change over the years (P = 0.114, data not shown). It is possible that in the later years of the study, more patients were diagnosed with in situ tumors, which has been shown in a previous publication [18], but these tumors were not the scope of the present study. Also, our time span was too small to show any differences.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…In our study, the frequencies of stages did not change over the years (P = 0.114, data not shown). It is possible that in the later years of the study, more patients were diagnosed with in situ tumors, which has been shown in a previous publication [18], but these tumors were not the scope of the present study. Also, our time span was too small to show any differences.…”
Section: Discussionmentioning
confidence: 78%
“…Our data come from patients treated from 2001 to 2008 at the Clinical Hospital of the Federal University of Minas Gerais (Hospital das Clínicas, Universidade Federal de Minas Gerais, HC-UFMG), Belo Horizonte, Brazil. The HC-UFMG is a general teaching hospital that treats mostly patients from the SUS coming from Belo Horizonte (the state’s capital) or from smaller cities without a tertiary health care center [18]. It provides patients with surgery as well as chemo- and endocrine therapies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Particularly, mastectomy has played an important role in this field, and it currently ranks among the most common treatments. In recent reports from Saudi Arabia (Al‐Gaithy et al., 2019 ) and Brazil (Balabram et al., 2012 ), its rates ranged from 62.4% to 64.6% of all procedures related to breast cancer in 2011 (Brazil) and 2018 (Saudi Arabia); in some provinces of China (Huang et al., 2016 ; Lu et al., 2015 ), these numbers went as high as 80.41%–81.7% in 2014.…”
Section: Introductionmentioning
confidence: 97%